3(9-8x-4x)+8(3x+4)=8

Simple and best practice solution for 3(9-8x-4x)+8(3x+4)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(9-8x-4x)+8(3x+4)=8 equation:


Simplifying
3(9 + -8x + -4x) + 8(3x + 4) = 8

Combine like terms: -8x + -4x = -12x
3(9 + -12x) + 8(3x + 4) = 8
(9 * 3 + -12x * 3) + 8(3x + 4) = 8
(27 + -36x) + 8(3x + 4) = 8

Reorder the terms:
27 + -36x + 8(4 + 3x) = 8
27 + -36x + (4 * 8 + 3x * 8) = 8
27 + -36x + (32 + 24x) = 8

Reorder the terms:
27 + 32 + -36x + 24x = 8

Combine like terms: 27 + 32 = 59
59 + -36x + 24x = 8

Combine like terms: -36x + 24x = -12x
59 + -12x = 8

Solving
59 + -12x = 8

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-59' to each side of the equation.
59 + -59 + -12x = 8 + -59

Combine like terms: 59 + -59 = 0
0 + -12x = 8 + -59
-12x = 8 + -59

Combine like terms: 8 + -59 = -51
-12x = -51

Divide each side by '-12'.
x = 4.25

Simplifying
x = 4.25

See similar equations:

| 5x+10x+2=32 | | 4x-17x-15=0 | | 4.5-12s=-5s | | 7b-2=54 | | (6x-4)=7(6x-4)+9 | | p^2+18p+6= | | 4x-2y+3z=3 | | [-2-x]=4 | | 8=-5f+3f | | 5-3(3-p)=7p | | -8=-3(7x-4)+1 | | 9x-10=5x-10+36 | | -17x=-306 | | 6-2h=h | | 5y+3y=56 | | 10y^2+15y-45=0 | | 8x-46=5x-7 | | 2(x-4)-11=24x-239 | | 5.2n=7.6+3.6n | | 8x+14=11x-28 | | -2-x=4 | | 13r=28 | | -7+m=-21 | | x^2+2y= | | 46=2x-8 | | 2x-(2x-1)=12 | | 4x-25=125 | | [3x-(4x-6)]=10 | | x^4+12x^3-10x^2-44x-18=0 | | 2(1x-3)=2x+5 | | 2x-(2x-1)=11 | | 125d^3-8p^3= |

Equations solver categories